Potential Development of Brayut Cultural Village, Sleman District, Yogyakarta - Ariadi, Adyanti Putri; Wihardyanto, Dimas; Roychansyah, Muhammad Sani (Jurnal Teknik Sipil dan Perencanaan, 2018)
Brayut Tourism Village is an agricultural and culture - based tourism village located in Sleman Regency. Thepotential of nature and culture is very interesting to be developed further. However, during its development, there aresome emerging issues which damage the environment and the life of Brayut Tourism Village society. The purpose of thisresearch is to maintain and preserve the potential for sustainable tourism of Brayut Village. This research used aqualitative descriptive method, including explaining development strategy covering various aspects, which are theenvironmental, sociocultural, and economic direction of physical and non-physical development. For the sake of thecontinuity of the uniqueness of nature and culture, Brayut Tourism Village that grows in the middle of Sleman Regencydevelopment area requires sustainable tourism management. The important element in the development of villagetourism is the involvement of villagers in every aspect of tourism activities in the village.